Study of Phytochemicals, Toxicity, Antibacterial Activity of Ethyl Acetate Leaf Extract Extract (Paperomiapellucida L) - Ida Duma Riris; Tita Juwitaningsih; Destria Roza; Marini Damanik; Albinus Silalahi (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Suruhan Leaf (Paperomiapellucida L) is a weedy plant that is used by rural communities as herbal medicine. In this study, phytochemical tests have identified compounds contained in the ethyl acetate extract, then the toxicity test was carried out by the Brint Shrimp LethallytyTocycity (BSLT) method using Artemia Salina Leach shrimp larvae, an antibacterial activity test for bacteria: Bacillus cereus (ATCC) 11778), S. aureus (ATCC 25923), E. coli (ATCC 25922), S. saprophytic (ATCC 49907), Catsobacterfrendi (ATCC 18090), P.acne (ATCC 27853), Epidermis (ATCC 12228) with diffusion methods, various of concentration 1; 5; 10; 25% as control used chloramphenicol 30 mcg, the highest inhibitory zone at a concentration of 25% showed a strong antibacterial succession of 20.7; 11.1; 29.7; 15; 13.5; 10; 17.3 mm. The results of the identification of compounds in ethyl acetate extract are alkaloids, flavonoids, steroids, saponins, and tannins. The toxicity of LC50 is 71.28 ppm (toxic).